2019
DOI: 10.3390/jcm8081116
|View full text |Cite
|
Sign up to set email alerts
|

Low Vitamin K Status Is Associated with Increased Elastin Degradation in Chronic Obstructive Pulmonary Disease

Abstract: Elastin degradation is accelerated in chronic obstructive pulmonary disease (COPD) and is partially regulated by Matrix Gla Protein (MGP), via a vitamin K-dependent pathway. The aim was to assess vitamin K status in COPD as well as associations between vitamin K status, elastin degradation, lung function parameters and mortality. A total of 192 COPD patients and 186 age-matched controls were included. In addition to this, 290 COPD patients from a second independent longitudinal cohort were also included. Vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 35 publications
3
44
0
Order By: Relevance
“…In the present study, an inverse correlation was found between vitamin K status and pDES in COVID-19 patients, suggesting a pathomechanistic link between vitamin K deficiency and accelerated elastolysis. This relationship has previously also been demonstrated in patients with COPD [15] and may be an indication for a link between vitamin K deficiency, insufficient MGP carboxylation and aberrant tissue remodeling in patients with COVID-19.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In the present study, an inverse correlation was found between vitamin K status and pDES in COVID-19 patients, suggesting a pathomechanistic link between vitamin K deficiency and accelerated elastolysis. This relationship has previously also been demonstrated in patients with COPD [15] and may be an indication for a link between vitamin K deficiency, insufficient MGP carboxylation and aberrant tissue remodeling in patients with COVID-19.…”
Section: Discussionsupporting
confidence: 62%
“…Measuring levels of dp-ucMGP has previously been proven to be a useful method to assess vitamin K status [22]. Dp-ucMGP inversely relates to mortality and other clinical meaningful endpoints in various cohorts [12,15,[23][24][25][26][27][28][29][30]. Supplementation of vitamin K has a reducing effect on dp-ucMGP levels [22,31], and the opposite holds true with regard of the use of VKAs [22,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has shown that reduced vitamin K status in COPD patients was associated with high mortality rates (39). The study also showed that elastin degradation is accelerated in chronic COPD and is partially regulated by Matrix Gla Protein (MGP), via a vitamin K-dependent pathway.…”
Section: Discussionmentioning
confidence: 96%
“…Although vegetables have been shown to have beneficial nutrients that can aid healthy lung structure (34,36,37), more research is warranted to link specific nutrients in the greens that can help protect the alveoli from developing emphysematous lung injuries. Since vitamin K is mostly obtained from dark green vegetable, it is highly likely that it may have an impact on the biology of lung airway or alveoli structure (38,39). Low intake of vitamin A also from dark green vegetables has been associated with COPD in different populations (40)(41)(42) and a few studies have shown the potential role of vitamin A in maintaining the integrity of the lung epithelium, non-emphysematous state and exerts anti-inflammatory effects (43,44).…”
Section: Introductionmentioning
confidence: 99%